The effect of music on pain management in preterm infants during daily painful procedures: a systematic review and meta-analysis - Ou, Yiran; Chen, Ling; Zhu, Xinyue; Zhang, Tianci; Zhou, Ye; Zou, Lu; Gao, Yun; Wang, Zhenghao; Zheng, Xiaofeng (Frontiers in Pediatrics, 2024)
The present systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to investigate the effects of music on pain management in preterm neonates during painful procedures.The PubMed, Embase, Web of Science, EBSCO and Cochrane Library databases were searched to identify relevant articles published from their inception to September 2023.The study search strategy and all other processes were implemented in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement.Four RCTs that satisfied the inclusion criteria were included in this meta-analysis. The music group had significantly lower Premature Infant Pain Profile (PIPP) scores during (RR= -1.21; 95% CI= -2.02--0.40, p= 0.0032) and after painful procedures (RR= -0.65; 95% CI= -1.06--0.23, p= 0.002). The music group showed fewer changes in PIPP scores after invasive operations than did the control group (RR= -2.06; 95% CI -3.16 --0.96; p= 0.0002). Moreover, our results showed that music improved oxygen saturation during (RR = 3.04, 95% CI = 1.64-4.44, P<0.0001) and after painful procedures (RR = 3.50, 95% CI = 2.11-4.90, P<0.00001). However, the change in peak heart rate during and after painful procedures was not statistically significant (RR= -12.14; 95% .In conclusion, this systematic review demonstrated that music interventions are effective for relieving procedural pain in preterm infants. Our results indicate that music can reduce stress levels and improve blood oxygen saturation. Due to the current limitations, large-scale, prospective RCTs should be performed to validate the present results.